Analisis Swot Untuk Menentukan Strategi Pengembangan Industri Batik (Studi Kasus: Kecamatan Laweyan Kota Surakarta) - Fiantoro, Muhammad Arifin Yusuf, Ir. Muchlison Anis.,MT, Indah Pratiwi, ST.,MT (2016)
Sentra Batik industry in Surakarta very famous are the District Lawiyan or Laweyan located in the western city of Surakarta. This district is famous for its population many became batik producers and traders, since the beginning until now. The purpose of this study is to identify industry profile Sentra Batik Industry in Sub Laweyan Surakarta and determine the development strategy of the sentra Batik Industry in Sub Laweyan Surakarta. This research using SWOT analysis method. With the SWOT analysis will be able to produce their several alternative strategies in making a good decision to run. So it can determine the batik industry development strategy. The results using SWOT of votes in batik Peacock Sweet IFAs with large batik industry classification of 3.12. IFAS Assessment at Putra Laweyan batik with batik medium industrial classification by 3.13. Rate EFAS at Merak Sweet batik with batik large industrial classification of 2.97. Rate EFAS at Putra Laweyan batik with batik industry classification medium of 3.01. Rate EFAS in Marin batik with batik small industrial classification of 0.82. Based on the results of SWOT analysis, the batik industry in Sub Laweyan namely batik industry Merak Manis, batik industry Putra Laweyan and Marin has been the path he had the right to continue to increase in sales.